ANALISIS DETERMINAN FAKTOR TABUNGAN (Studi Kasus Desa Panggel dlangu Butuh, Purworejo, Jawa Tengah) - Unggul Priyadi; Taufiq Hidayat (UII, 2016)
Household consumers always have a need for current and future needs. To full fill future needs is done by creating savings. Through ownership savings can protect emergency matters and other necessities to in the future. This study aimed to analyze the effect of income, savings interest rate, number of family, education, transaction costs and the type of work on the number of household savings in the village Panggeldlangu, Purworejo, Central Java. Data analysis method used is multiple regression with a sample of 71 households. One of the result of research is income, savings interest rate, number of family members, education, transaction costs and the kind of work simultanous significant effect on the amount of the savings. Meanwhile partially variable of family size is negative effect, while the variables of income, education of household head, and transaction costs are the positive effect, but variable interest rate savings and the type of work did not significantly affect household saving.